Proliferation is a central independent prognostic factor and target for personalized and risk-adapted treatment in multiple myeloma - Hose, Dirk; Rème, Thierry; Hielscher, Thomas; Moreaux, Jérôme; Messner, Tobias; Seckinger, Anja; Benner, Axel; Shaughnessy, John D.; Barlogie, Bart; Zhou, Yiming; Hillengaß, Jens; Bertsch, Uta; et al. (Haematologica, the hematology journal, 2011)
Background Proliferation of malignant plasma cells is a strong adverse prognostic factor in multiple myeloma and simultaneously targetable by available (e.g. tubulin polymerase inhibitors) and upcoming (e.g. aurora kinase inhibitors) compounds.Design and Methods We assessed proliferation using gene expression-based indices in 757 samples including independent cohorts of 298 and 345 samples of CD138-purified myeloma cells from previously untreated patients undergoing high-dose chemotherapy, together with clinical prognostic factors, chromosomal aberrations, and gene expression-based high-risk scores.Results In the two cohorts, 43.3% and 39.4% of the myeloma cell samples showed a proliferation index above the median plus three standard deviations of normal bone marrow plasma cells. Malignant plasma cells of patients in advanced stages or those harboring disease progression-associated gain of 1q21 or deletion of 13q14.3 showed significantly higher proliferation indices; patients with gain of chromosome 9, 15 or 19 (hyperdiploid samples) had significantly lower proliferation indices. Proliferation correlated with the presence of chromosomal aberrations in metaphase cytogenetics. It was significantly predictive for event-free and overall survival in both cohorts, allowed highly predictive risk stratification (e.g. event-free survival 12.7 versus 26.2 versus 40.6 months, P
Gesehen am 30.06.2022